Sisters of Charity Training on the Latvian Territory in the 19th Century - Fokina, Olga; Millere, Inga; Circenis, Kristaps; Deklava, Liāna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In 1772 Daugavpils(Dyneburg) was incorporated into the Russian Empire and remained the main city of the province of Daugavpils. In 1796 it was incorporated into Belarus province and later in 1802 into Vitebsk province. In 1864 16 countries joined officially the First Geneva Convention, For the Amelioration of the Condition of the Wounded and Sick in Armed Forces in the Field”. In 1867 Russia including Latvia also joined the Geneva Convention. That yearthe Russian association for wounded and sick soldiers care wasestablished. Over timethe Russian association for wounded and sick soldiers carechanged its original name. In 1879 it was given the new official name, the Russian Red Cross Society”.The Committeesof the Russian Red Cross were established in all the provincesof Russiangubernias, so in Vidzeme and Kurzeme they were in Riga and Jelgava, but Latgale was under the control of the Committee of Vitebskgubernia. The communities of the Red Cross charity of Mercywerefounded to prepare the female sanitary staff for the medical care of the sick and the wounded during the war and to provide nursing care in hospitals, military hospitals and private homes during peacetime. The Vitebsk local committee of the Russian Red Cross supported the activities of Charity Nurses Community in Vitebsk.